Essential Infectious Disease Topics for Primary Care - Skolnik, Neil S.; Albert, Ross H.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2008)
Although infectious disease mortality is decreasing, the disease burden remains substantial as many new infections have been identified and some well-established infectious diseases have reemerged. This book provides an easy-to-use, practical, yet comprehensive resource for family practitioners to use in the daily struggle against infectious diseases. It discusses vaccines and preventive measures as well as information on how to reduce the incidence of antimicrobial-resistant organisms by judiciously prescribing antibiotics and informing patients about the appropriate use of these agents.
Upper Respiratory Tract Infections -- Clinical Guidelines -- Pharyngitis -- Treatment and Management of Acute Otitis Media -- Management of Chronic Obstructive Pulmonary Disease Exacerbations and Acute Bronchitis -- 5 Latent Tuberculosis Infection: Testing and Treatment -- Acute Sinusitis -- Gastrointestinal Infections -- Gastroenteritis -- Hepatitis -- Sexually Transmitted Diseases -- Sexually Transmitted Diseases -- Human Immunodeficiency Virus -- Skin, Bone, and Joint Infection -- Cellulitis and Skin Infections Associated with Bites -- Diabetic Foot Infections -- Osteomyelitis -- Septic Arthritis and Infectious Bursitis -- Lyme Disease Prevention, Diagnosis, and Treatment -- Other Infectious Disease Topics -- Infective Endocarditis -- Meningitis -- Urinary Tract Infections -- Adult Immunizations -- Clinical Ethics and Infectious Disease in Family Medicine.
Keywords: Medicine; General practice (Medicine).; Infectious diseases; Primary care (Medicine).; Medicine & Public Health; Infectious Diseases; Primary Care Medicine; General Practice / Family Medicine; Electronic books